Late Cretaceous paleomagnetic data from the Median Range of Kamchatka, Russia: tectonic implications (Dataset) ... - Levashova, Natalia M; Shapiro, Mikhail N; Bazhenov, Mikhail L (Magnetics Information Consortium (MagIC), 2006)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Late Cretaceous paleomagnetic data from the Median Range of Kamchatka, Russia: tectonic implications ...